Synthesis of Pb2Fe2O5 by thermal decomposition of Pb2[Fe(CN)6]4H2O - Gil, Diego Mauricio (2010)
In the present work the synthesis, thermal analysis and structural charaterization of Pb2[Fe(CN)6]4H2O are described in order to obtain mixed oxides with technological properties. The starting materials and the decomposition products were characterized by IR spectroscopy, powder X.ray diffraction and scanning electron microscopy.